Comparative characteristics of hormonal profiles in autonomic-dyshormonal myocardial dystrophy of various ethiology - V. R. Mkrtchyan (Российский кардиологический журнал, 2005)
The aim of the study was to identify the changes in estradiol, progesterone, testosterone, luteotropic (LTH), follicle-stimulating (FSH), thyreotropic (TTH) hormones, prolactin, triiodothyronine (T3), and thyroxine (T4) in autonomicdyshormonal myocardiodystrofy (ADM) of various ethiology. Hormone levels were measured in 52 menopausal women with pathological climax, women with uterine fibromyoma (n=45), premenstrual syndrome, PMS (n=36), and with post-castration syndrome (n=42). Mean estradiol level in ADM of various genesis was close to lower norm limit. Estradiol level disturbances were identified in more than 50% of all cases, typically manifesting in lower concentrations. High prevalence of normal estradiol levels in all four groups was an evidence of ADM pathogenesis complexity. Progesterone and testosterone levels were also not significant in ADM development. In uterine myoma and, to a lesser extent, in PMS, increased LTH levels were more prevalent. In PMS and, especially, in uterine myoma, FSH levels were usually elevated. Nevertheless, the role of these disturbances in ADM pathogenesis is still understudied. Mean prolactin level in myoma patients was higher than normal or that in ADM of another genesis. TTG, T3, and T4 levels in all four groups were normal, and couldn't play a significant role in ADM development.